Collaboration of Stakeholders as a Model for the Protection and Sustainable Management of Peatland Ecosystems - Owin Jamasy, Djamaludin; Gunawan, Haris; Budisusanti, SPM; Askary, Muhammad; Suwendar, Agus (2023)
The protection and management of empowerment-based peatland ecosystems prioritizes the principles of education, participation, contribution and local wisdom. The purpose of this study is to understand the importance of collaborative multistakeholders roles in the process of achieving the output of peatland ecosystem sustainability projects. The collaborative role of stakeholders is a joint commitment to prevent various disasters such as droughts, loss of carbon stocks, and loss of biodiversity habitats. Building collaboration from the role of multistakeholders in the process of facilitation and empowerment-based assistance is an important factor in achieving the success of the SMPEI project in Tapak/Village. The TK-PPEG institutions as a forum for community participation and empowerment are strategic and appropriate solutions to implement the agreed programs as stated in the community work plan document (RKM); In addition, the collaboration of the multistakeholders, is important as a process of transfering community knowledge and skills in this project. The role of the collaboration among multi-stakeholders is a strategic model and a leading alternative to sustainable efforts in protecting and managing peatland ecosystems.